Evaluation of equine assisted learning in education for primary school children: a qualitative study of the perspectives of teachers - Stoppard, Lorna; Donaldson, Jayne (Frontiers in Education, 2024)
The study presents qualitative research on the impact of Equine Assisted Learning in Education (EALE) has on the development of life skills in children as perceived by teachers and programme trainer. It used a qualitative approach using semi structured interviews with eight participants to find what aspects of the programme worked (or not), if changes in cognitive, psychomotor or social skills were witnessed during and or after the EALE in the children and what experiences teachers and programme trainers report about the EALE. There were examples of immediate impact for the children, and this impact was often evident for months after the intervention. This involved aspects of travelling to and from the programme, activities away from the horses and activities with the horses. There were no negative aspects of the programme identified, apart from the further availability of such a programme to children within each council area. The teachers' experiences of EALE were viewed as an excellent means of engaging children in learning.